2020
DOI: 10.1111/nin.12349
|View full text |Cite
|
Sign up to set email alerts
|

‘The Problem of the Color Line’: Faculty approaches to teaching Social Justice in Baccalaureate Nursing Programs

Abstract: Social justice is put forth as a core professional nursing value, although conceptualizations within foundational documents and among nurse educators remain inconsistent and contradictory. The purpose of this study was to explore how faculty teach social justice in theory courses in Baccalaureate programs. This qualitative study utilized constructivist grounded theory methods to examine processes informing participants' teaching. Participants utilize four overarching approaches: fostering engaging classroom cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Furthermore, silently reproducing Eurocentric worldviews enables nurse researchers and educators to ignore the complexities that underpin and uphold systemic racism. Yet, this apolitical lens ultimately prevents the examination of root causes of inequities and undermines the very ideals of social justice that we aim to uphold (Valderama-Wallace & Apesoa-Varano, 2020). Underpinning educational endeavours with nursing's aims of social justice must therefore be inclusive of the contextual elements that influence teaching and learning.…”
Section: Macro-level Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, silently reproducing Eurocentric worldviews enables nurse researchers and educators to ignore the complexities that underpin and uphold systemic racism. Yet, this apolitical lens ultimately prevents the examination of root causes of inequities and undermines the very ideals of social justice that we aim to uphold (Valderama-Wallace & Apesoa-Varano, 2020). Underpinning educational endeavours with nursing's aims of social justice must therefore be inclusive of the contextual elements that influence teaching and learning.…”
Section: Macro-level Challengesmentioning
confidence: 99%
“…Consistent with Chinn (2018b), students were enabled to be active participants in the grading process. Such assessment strategies and intentional democratizing of the classroom were an attempt to move beyond traditional teaching tactics toward strategies that allow students the space to demonstrate self-reflective learning and transformation (Valderama-Wallace & Apesoa-Varano, 2020).…”
Section: Demystificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our concern is that being able to take actions should follow an interpretation based on something other than personal values and backgrounds (cf. Valderama-Wallace and Apesoa-Varano, [66,67]), also with the risk that GH content becomes 'fluid' and related to partial issues, while not being related to any social context, understanding and explanations. In our data, we found that GH, as expressed in the course syllabi, are not understood, discussed or interpreted underpinned by any explicit theoretical approach.…”
Section: Lack Of Theoretical Perspectivementioning
confidence: 99%
“…Among the obstacles are the background of nursing educators and their relative status within their institutions. In a study of US nursing educators' experiences teaching social justice content on undergraduate nursing programmes (Valderama-Wallace and Apesoa-Varano [67]), educators who wished to stress the issues felt isolated at their workplace and the educators' backgrounds were significant for how content was taught. Some studies have been made on race and ethnic background among nurse educators [77,78], but we were unable to find research on nurse educators' prior education with respect to sustainability studies, environmental determinants of health, personal experience of living in communities exposed to environmental hazards or prior experience working with environmental justice.…”
Section: Obstacles To Including Gh Ej and Sdh In Nursing Curriculamentioning
confidence: 99%